The Supramolecular Attitude of Metal–Salophen and Metal–Salen Complexes - Luca Leoni (Inorganics, 2018)
In this review we cover some aspects of metal–salophen and metal–salen complex chemistry related to their supramolecular attitude. We examined under the lens of the non-covalent interactions their potential to behave as building blocks for auto-assembled architectures, supramolecular receptors and catalysts, although this last point has been only briefly mentioned.